Give up control to gain control. Issue 8 (26th March 2019) - Hodges, Dawn Z.
Abstract : "I'll admit it's somewhat paradoxical to gain control by giving it up, but give it a try. You might find it works, " writes Justin Kitch, chief executive officer ofcurious.com, in Fortune .